Use Of Economic Problems In Mathematics Textbooks In Elementary Grades - Nasriddinova Gulshodakhan (Genius Journals, 2024)
This scientific article is adapted to mathematics textbooks for design classes. The integration of real economic processes into the mathematics curriculum not only increases the mathematical development of material students, but also helps to further increase economic opportunities from an early age. The introduction of economic issues into primary education, the study of problems and pedagogical issues, this article aims to comprehensively develop and increase the importance of interdisciplinary education for educated students
Keywords: Economic issues; Mathematics education; Primary grades